2021
DOI: 10.3389/fphar.2021.771555
|View full text |Cite
|
Sign up to set email alerts
|

Large Screening Identifies ACE2 Positively Correlates With NF-κB Signaling Activity and Targeting NF-κB Signaling Drugs Suppress ACE2 Levels

Abstract: Coronaviruses SARS-CoV-2 infected more than 156 million people and caused over 3 million death in the whole world, therefore a better understanding of the underlying pathogenic mechanism and the searching for more effective treatments were urgently needed. Angiotensin-converting enzyme 2 (ACE2) was the receptor for SARS-CoV-2 infection. In this study, we found that ACE2 was an interferon-stimulated gene (ISG) in human cell lines. By performing an ISG library screening, we found that ACE2 levels were positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, a positive correlation between ACE2 and Nf-kB expression has been previously demonstrated, supporting the concept that targeting Nf-kB signaling can also inhibit ACE2 expression [ 56 ].…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, a positive correlation between ACE2 and Nf-kB expression has been previously demonstrated, supporting the concept that targeting Nf-kB signaling can also inhibit ACE2 expression [ 56 ].…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have shown that CEP acts on host cells to interfere with viral infection by affecting the expression of the viral receptor ACE2 (angiotensin-converting enzyme 2) ( Chitsike et al., 2021 ; Yan et al., 2021 ). In our study, we found that CEP interfered with PDCoV infection by acting on the host cell rather than the virus.…”
Section: Resultsmentioning
confidence: 99%
“…The binding affinity between the receptor and the viral protein affects the efficiency of viral infection in target cells ( Morizono et al., 2011 ). A previous study reported a significant reduction of symptoms in COVID-19 patients administered an angiotensin-converting enzyme inhibitor ( Yan et al., 2021 ). The mutation of key residues on APN significantly affects the infection efficiency of PDCoV ( Ji et al., 2022 ).…”
Section: Introductionmentioning
confidence: 96%
“…Using human cell models, Yan and his colleagues [ 77 ] found that the stimulation of RLRs with viral RNA mimic poly(I:C) or viral DNA mimic poly(dA:dT) increases the level of both ACE2 mRNA and protein, 13 ISGs promote its expression (especially ISG95), and finally, four of them (ISG10, ISG52, ISG71, and ISG95) can significantly enhance the NF-κB level. All these data suggest that ACE2 behaves like an ISG and its level correlates positively with NF-κB activities [ 77 ]. Thus, it is possible that the recognition of the Spike protein by TLR4 participates in the IFN-I response, which, in turn, improves ACE2 expression.…”
Section: Reviewmentioning
confidence: 99%
“…The type-I IFN response can be even more deleterious as ISG95 will induce ACE2 expression (while elevating NF-kB levels) [ 77 ], enabling the virus to infect cells that may not have originally been accessible to it, much like macrophages and peripheral blood immune cells [ 78 ]. The other potentially harmful effect of the type-I IFN response is the production of a truncated form of ACE2 (dACE2) via ISG15 [ 34 , 72 ].…”
Section: Reviewmentioning
confidence: 99%